Reliability of maternal recall of delivery and immediate newborn care indicators in Sarlahi, Nepal - Emily D. Carter; Karen T. Chang; Luke C. Mullany; Subarna K. Khatry; Steven C. LeClerq; Melinda K. Munos; Joanne Katz (BMC Pregnancy and Childbirth, 2021)
Abstract Background The intrapartum period is a time of high mortality risk for newborns and mothers. Numerous interventions exist to minimize risk during this period. Data on intervention coverage are needed for health system improvement. Maternal report of intrapartum interventions through surveys is the primary source of coverage data, but they may be invalid or unreliable. Methods We assessed the reliability of maternal report of delivery and immediate newborn care for a sample of home and health facility births in Sarlahi, Nepal. Mothers were visited as soon as possible following delivery (< 72 h) and asked to report circumstances of labor and delivery. A subset was revisited 1–24 months after delivery and asked to recall interventions received using standard household survey questions. We assessed the reliability of each indicator by comparing what mothers reported immediately after delivery against what they reported at the follow-up survey. We assessed potential variation in reliability of maternal report by characteristics of the mother, birth event, or intervention prevalence. Results One thousand five hundred two mother/child pairs were included in the reliability study, with approximately half of births occurring at home. A higher proportion of women who delivered in facilities reported “don’t know” when asked to recall specific interventions both initially and at follow-up. Most indicators had high observed percent agreement, but kappa values were below 0.4, indicating agreement was primarily due to chance. Only “received any injection during delivery” demonstrated high reliability among all births (kappa: 0.737). The reliability of maternal report was typically lower among women who delivered at a facility. There was no difference in reliability based on time since birth of the follow-up interview. We observed over-reporting of interventions at follow-up that were more common in the population and under-reporting of less common interventions. Conclusions This study reinforces previous findings that mothers are unable to report reliably on many interventions within the peripartum period. Household surveys which rely on maternal report, therefore, may not be an appropriate method for collecting data on coverage of many interventions during the peripartum period. This is particularly true among facility births, where many interventions may occur without the mother’s full knowledge.